KINESIOLOGY EXERCISES AS A MEANS OF DEVELOPMENT OF CHILDREN WITH DOWN SYNDROME OF PRESCHOOL AGE (Physical Culture and Sport: Scientific Perspective, 2025)
The problem of children's disability is very urgent. Every year, more and more children are born with a diagnosis such as Down syndrome. It is known that children with Down syndrome reach the main stages of motor development later, and the age range of development of each skill is greater in them than in children without disabilities. We determined that kinesiology is quite popular today. It is practiced both in psychocorrection and physical therapy of children of different ages. Experts emphasize that the most positive effect of the use of kinesiology exercises on a child's development is noted precisely in preschool childhood. It was determined that the purpose of kinesiology exercises is to help align and synchronize the work of the left and right hemispheres of the brain, form attention and memory, facilitate the process of reading and writing, help better orientation in space, and help the child adapt to the learning process. The models and approaches regarding the influence of kinesiological exercises on the child's development were analyzed, the essence and specificity of such exercises, their purpose and effect on the body of preschool children with Down's syndrome were revealed. A block diagram used in the kinesiotherapy practice of children with Down's syndrome of preschool age is proposed. The results of the use of kinesiology exercises demonstrate that they are an effective tool for children with Down syndrome of preschool age, because they improve the development of motor functions, selfcare skills, hand functioning and communication properties. Regularly practicing kinesiological exercises helps improve muscle tone, joint stability, and motor coordination, which significantly enhances their ability to perform functional movements. A well-designed kinesiological training program, tailored to the individual needs of each child, can lead to significant progress in motor and cognitive abilities. Combining exercises for gross and fine motor skills with elements of play therapy and sensory integration techniques enhances engagement and motivation. The interdisciplinary approach, involving physiotherapists, occupational therapists, and educators, ensures the most effective results.
Keywords: Down's syndrome; kinesiological exercises; kinesiotherapy; children